(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Considering the increase in energy consumption and issues related to air pollution by chemical residues and global warming caused by the consumption of fossil fuels resulting from that combustion, many approaches have been considered to reduce the use of fossil fuels and the use of renewable energies at this time. Efficient use of energy, energy storage and management is critical because portable power sources are environmentally friendly as well as provide economic cost and reduce dependence on fossil fuels. One of the most important commodities available for energy storage is the battery. Various electrochemical lithium batteries are used in series to achieve the voltage required for applications such as electric vehicles, industrial power systems, military purposes, etc. Batteries used in a series will have differences in capacity due to factory conditions, the environment, the chemical involved in its manufacture, especially lithium, and the number of times of charging and discharging, this series of batteries will move towards an imbalance of voltage and capacity. This is an incentive to create and develop battery power system management and an integrated charging system, to balance batteries and increase their capacity, efficiency and life. The purpose of this research is to stimulate the establishment and development of an integrated charging system for the lithium-ion battery, and to balance the batteries and increase their capacity, efficiency and life, In addition, proposals will be presented to design a high-efficiency charger with typical electrochemical components and standard specifications, to provide an optimal solution for those battery chargers